MODEL PENINGKATAN KINERJA PENJUALAN MELALUI INTERPERSONAL SKILLS, SALESMANSHIP SKILLS DAN TECHNICAL SKILLS SALESPERSON - Winarto, Winarto (Admisi dan Bisnis, 2018)
Sales performance has significant role toward marketing performance of a company. Sales performance is constitutedfrom the resultan of salesperson performance in a company. The purpose of this research is to build sales management  model in order to increase sales perfomance  through promoting interpersonal skills, salesmanship  and technical skills of salesperson. Questionnaire is used for collecting data from the salesperson. Multiple linier regression is used to analyze data. The results of this reseach show that interpersonal skills, salesmanships skills and technical skills of salesperson have positive impact toward sales perfomance. Thus, the sales management model is properly  implemented by a company.